Plan de negocio para la creación de una empresa comercializadora de textos especializados para odontólogos - Matute García, Cristóbal Daniel (2016)
This business plan seeks to determine the viability of a company dedicated to the commercialization of printed books for dentists, who work in the city of Quito, the valley of Los Chillos, Cumbayá and Tumbaco. Along with the books, the company will provide its customers access to a virtual library where they will find cases of patients documented in text, images and videos which show the practical application of the theory expounded in books. Some investigation techniques and analysis tools learned throughout the university years were applied in the development of this plan. The PESTLE model showed a favorable external environment and the application of Porter five forces revealed that there is a poor amount of competitors. In the customer analysis, qualitative and quantitative methods were used and showed a clear idea of dental books buyers behavior. After the investigation is known that dentists are predisposed to buy printed books, which was confirmed by the 90% of the interviewed sample.